Microscopically crumpled indium-tin-oxide thin films as compliant electrodes with tunable transmittance - Ong, Hui-Yng (2015)
Indium-tin-oxide (ITO) thin films are perceived to be stiff and brittle. This letter reports that crumpled ITO thin films on adhesive poly-acrylate dielectric elastomer can make compliant electrodes, sustaining compression of up to 25% × 25% equi-biaxial strain and unfolding. Its optical transmittance reduces with crumpling, but restored with unfolding. A dielectric elastomer actuator (DEA) using the 14.2% × 14.2% initially crumpled ITO thin-film electrodes is electrically activated to produce a 37% areal strain. Such electric unfolding turns the translucent DEA to be transparent, with transmittance increased from 39.14% to 52.08%. This transmittance tunability promises to make a low-cost smart privacy window.